EFFECT OF PH AND ORGANIC LIGANDS ON THE KINETICS OF SMECTITE DISSOLUTION AT 25 °C - Golubev S.V.; Pokrovsky O.S.; Bauer A. (My University, 2006)
Forward dissolution rates of Na-Montmorillonite (Wyoming) SWy-2 smectite (Ca0.06Na0.56)[Al3.08Fe(III) 0.38Mg0.54] [Si7.93 Al0.07]O20(OH)4 were measured at 25 °C in a mixed-flow reactor equipped with interior dialysis compartment (6-8 kDa membrane) as a function of pH (1-12), dissolved carbonate (0.5-10 mM), phosphate (10-5 to 0.03 M), and nine organic ligands (acetate, oxalate, citrate, EDTA, alginate, glucuronic acid, 3,4-dihydroxybenzoic acid, gluconate, and glucosamine) in the concentration range from 10-5 to 0.03 M. In organic-free solutions, the Si-based rates decrease with increasing pH at 1 ≤ pH ≤ 8 with a slope close to -0.2. At 9 ≤ pH ≤ 12, the Si-based rates increase with a slope of ~0.3. In contrast, non-stoichiometric Mg release weakly depends on pH at 1 ≤ pH ≤ 12 and decreases with increasing pH. The empirical expression describing Si-release rates [R, mol/cm2/s] obtained in the present study at 25 °C, I = 0.01 M is given byR = 2.2 · 10- 17 · aH+0.21 + 1.0 · 10-20 + 6 · 10- 17 · aOH-0.33At circum-neutral pH, the Si-release-based dissolution is promoted by the addition of the following ligands ranked by decreasing effectiveness: EDTA > 3,4-DHBA > citrate ≥ oxalate. Phosphate, glucuronate, glucosamine, gluconate, alginate, and acetate act as inhibitors of dissolution and HCO3-, CO32- exhibit no effect on dissolution rate. Non-stoichiometric, non-steady-state Mg release was very weakly affected by the presence of ligands. Analysis of reacted solid products using XRD, FT-IR, and XPS revealed no major change in structure, surface chemical composition or specific surface area as a function of pH, ligand concentration, and duration of experiments. Ligand-affected rates re-calculated to constant pH were interpreted using a phenomenological equation which postulates the Langmurian adsorption of a ligand on surface sites. Overall, results of this study demonstrate that very high concentrations (0.001-0.01 M) of organic ligands, whether they are originated from organic matter enzymatic degradation or bacterial metabolic activity are necessary to appreciably affect smectite dissolution. As a result, the effect of natural organics on the weathering rate of smectite is expected to be weak. © 2006 Elsevier Inc. All rights reserved.